2020
DOI: 10.3390/ijerph17051620
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Bone Mineral Density, Physical Activity and Nutritional Intake in Middle-Aged Women with High Levels of Arterial Stiffness: A Pilot Study

Abstract: There is little consensus regarding the impacts of physical activity and nutrient intake on bone mineral density (BMD) in subjects with high or low levels of arterial stiffness. This study was performed to investigate whether physical activity and nutrient intake are associated with BMD in middle-aged women with high levels of arterial stiffness. The study population consisted of middle-aged women aged 40-64 years (n = 22). BMD was assessed by dual-energy X-ray absorptiometry. Carotid-femoral pulse wave veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
(95 reference statements)
0
6
0
1
Order By: Relevance
“…In this study, low PA was found to be significantly associated with an increased risk of OA. In addition, elevated DII was significantly associated with low PA (43) . Therefore, our results indicated that individuals with elevated levels of systemic inflammation may be less likely to exercise moderately or vigorously every week than those without.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, low PA was found to be significantly associated with an increased risk of OA. In addition, elevated DII was significantly associated with low PA (43) . Therefore, our results indicated that individuals with elevated levels of systemic inflammation may be less likely to exercise moderately or vigorously every week than those without.…”
Section: Discussionmentioning
confidence: 89%
“…Sample size varied from 22 to 5184 with an average of n = 862 ± 1379. Overall the combined sample from included studies was 54% male, with two studies including only females [ 39 , 47 ] and seven including only male participants [ 33 35 , 38 , 48 50 ]. Mean age varied from 21 to 78 years (overall mean 51 ± 7.3 years).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies measured hPA exposure using accelerometers [ 28 , 30 , 31 , 33 , 36 , 37 , 44 , 45 , 47 , 49 , 51 55 ], and 16 measured hPA via self-report questionnaire or interview [ 27 , 30 , 34 36 , 38 40 , 42 , 43 , 46 , 48 , 50 , 56 58 ]. Two studies [ 30 , 36 ] utilised both self-report and accelerometer to measure hPA reporting results separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…дозволяють припустити, що МЩКТ у жінок середнього віку з високим рівнем артеріальної жорсткості може бути пов'язана як з низькою фізичною активністю, так і з особливостями споживання ненасичених жирних кислот. Рекомендації щодо фізичної активності та харчування для профілактики порушень МЩКТ, ймовірно, повинні враховувати жорсткість артерій [57].…”
Section: взаємозв'язок артеріальної жорсткості судинної кальцифікації...unclassified